Does the FIFA World Cup`s congested fixture program affect players` performance? - Silva, J. R.; Rumpf, M.; Hertzog, M.; Nassis, G. (Asian Journal of Sports Medicine, 2017)
Background: The tournament design of any FIFA World CupTM is characterized with a high amount of games within a short period of time with limited recovery periods. This study aimed to investigate alterations in match activity and fatigue patterns of players from top ranked teams during the 2014 FIFA World Cup in Brazil.